THE LEVEL OF IMPLEMENTATION OF THE DEPARTMENT OF ENERGY PROGRAM FROM THE PERSPECTIVE OF PERSONNEL OF DOE: BASIS FOR SUSTAINABLE AND ACCESSIBLE ENERGY FOR TPHILIPPINES - Elahi, Malek (International Journal of Contemporary Economics and Administrative Sciences, 2020)
Background and Objective: This study is aimed at determining the implementation level of the DOE Programs in terms of Downstream Oil Industry; Alternative Technologies and Fuels; Indigenous Energy Development; Energy Conservation and Efficiency; Renewable Energy; Power and Rural Electrification; and Overall Energy Plans. Material and Methods: The study is survey type and a questionnaire was distributed among the personnel assigned in the National Capital Region and the 3 divisions of Philippine archipelago namely Mindanao, Visyas, and Luzon, covering the last quarter of 2017 until the second quarter of 2018. The input box was consisted of the determination of the level of implementation of the DOE Programs in philippines. The Process box involved data collecting procedures from the personnel by descriptive evaluative survey supported by interviews as the basis of interpreting the study outcome. Then the data was encoded and the results were subjected to statistical treatment for interpretation and analysis. Finally, the output box pertained to the proposed acceptable and sustainable energy for Philippines. Results and Conclusion: The overall composite weighted mean of the assessment in all 4 groups were described as “Implemented”. Moreover, all the above-mentioned items except number 7 were considered “strength”. The perceptions of the level of implementation were identical. This is an indicator that the personnel has the common perception of the implementation of DOE programs.